Modelling the effects of the weather on admissions to UK trauma units: a cross-sectional study. Issue 10 (22nd November 2010) - Parsons, Nick; Odumenya, Michelle; Edwards, Antoinette; Lecky, Fiona; Pattison, Giles
Abstract : Objective: To assess the relationship between daily trauma admissions and observed weather variables, using data from the Trauma Audit and Research Network of England and Wales and the UK Meteorological Office. Design: A cross-sectional study. Setting: Twenty-one accident and emergency departments (ED) located across England. Participants: All patients arriving at one of the selected ED, with a subsequent death, inpatient stay of greater than 3 days, interhospital transfer or requiring critical care between 1 January 1996 and 31 December 2006. Main Outcome Measures: Daily counts of adult and paediatric trauma admissions. Results: Multivariate regression analysis indicated that there were strong seasonal trends in paediatric (χ 2 likelihood ratio test p<0.001), and adult (p=0.016) trauma admissions. For adults, each rise of 5°C in the maximum daily temperature and each additional 2 h of sunshine caused increases in trauma admissions of 1.8% and 1.9%. Effects in the paediatric group were considerably larger, with similar increases in temperature and hours of sunshine causing increases in trauma admissions of 10% and 6%. Each drop of 5°C in the minimum daily temperature, eg, due to a severe night time frost, caused adult trauma admissions to increase by 3.2%. Also the presence of snow increased adult trauma admissions by 7.9%. Conclusion: This is the largest study of its kind to investigate and quantify the relationship between trauma admissions and the weather. The results show clear associations that have direct application for planning and resource management in UK ED.